Sun Tracking Otomatis Untuk Pembangkit Listrik Tenaga Surya (PLTS) - Sigit Nurharsanto; Adhy Prayitno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Electricity has been used by industry, offices, as well as for the general public and individuals that is greatly improved in demand source of theelectricity can be obtained from solar energy converted into electrical energy by utilizing solar panels. The solar power can be utilized as an alternative electric energy, in utilizing this solar energy is by using a photovoltaic process,which converts directly solar energy into electrical energy.An automatic sun tracking for solar power plants can be designed to meet the needs of large-scale households which people can be easity to use itstechnology, This technology can be designed using some basic instruments such as solar panels. LDR (Light Dependent Resistor), Arduino microcontroller, motor AC and Motor Drivers. Some components are assembled and programmed into a sun tracking device that is called sun tracking,In this research the sun tracking used an automatic motion which following the direction of sunlight using arduino uno brain. The sunlight on LDR sensor and direct motor driver gave the command ‘’On’’ to a DC motor that would move the solar panel to always perpendicular to the arrival of sunlight. Therefore, the solar panels with automatic suntracking system in this research is obtained a control system that can work maximally in the process of controlling and revealed the maximum current.Keywords : Microcontroller, LDR, DC Motor, Solar Panel,Photovoltaics